Molecular sequence data of Thecaphora frezii affecting peanut crops in Argentina - Conforto, Erica Cinthia; Cazon, Luis Ignacio; Fernandez, Franco Daniel; Marinelli, Adriana; Oddino, Claudio; Rago, Alejandro Mario (Springer, 2018)
In Argentina, Thecaphora frezii is the causal agent of peanut smut, causing severe yield losses in peanut growing areas. In this work sequence data of the large ribosomal subunit (28S rDNA) of four T. frezii specimens from different production regions are provided. A fragment of about 650 bp was amplified by PCR from each of the isolates analyzed. The analysis of the sequences demonstrated 100 % identity among the four specimens and 92–96.3 % identity with sequences of other species of Thecaphora. This is the first study on molecular sequences of this pathogen.